Spirulina microalgae blend with biohydrogen and nanocatalyst TiO2 and Ce2O3 as step towards emission reduction: Promoter or inhibitor. (15th February 2023) - Shanmuganathan, Rajasree; Chi, Nguyen Thuy Lan; Chinnathambi, Arunachalam; Salmen, Saleh H.; Jhanani, G.K.; Gavurová, Beata; Sekar, Manigandan; Pugazhendhi, Arivalagan; Praveenkumar, T.R.
Highlights: Nanoparticles such as TiO2 and Ce2 O3 has been examined with biohydrogen. Combustion rates were increased owing to enhanced oxygen concentration. Inclusion of hydrogen increases both in-cylinder pressure and HRR, which leads to the formation of NOx. TiO2 and Ce2 O3 reduces the formation of pollutants. Abstract: Extensive use of fossil fuels is the main cause for global warming. Burning of fossil fuels increases the air pollution which leads to adverse human health effects. Biodiesel is one the promising source of the energy to replace fossil fuel. The current study focused on one of the most sustainable microalgae biodiesel blends in the diesel engine. Further, the nanoparticles such as TiO2 and Ce2 O3 were sonicated with the blends at the rate of 50 ppm to increase the brake thermal efficiency with least production of the pollutants. In addition to above, the hydrogen is also used as the secondary fuel to enhance the performance and combustion characteristics of the spirulina biodiesel. The constant hydrogen flow rate of 10 L/min was maintained throughout the study. Compared to the diesel fuel, biodiesel blends reported higher BTE due to the oxygenated additives and hydrogen addition. The maximum thermal efficiency for blend B30TH was found to be 29.5 % and minimum specific fuel consumption has been obtained for B30CH at maximum brake power conditions. In all test conditions, the biodiesel blends with hydrogen reported higher in-cylinder pressure and heat release rate. With regard to the emission, adding the biodiesel blends increases the combustion rates which leads to the reduction of accumulation of pollutants such as carbon monoxide, carbon dioxide, hydrocarbons, nitrogen of oxides and smoke. Among the various blends B20CH reported a massive reduction in the emission than B20TH.